Utilização de extrato de pimenta-da-jamaica (pimenta dioica L.) como antioxidante em carne mecanicamente separada (CMS) de frango - Gomes, Ligiane Maria de Carvalho (2015)
This work aimed to evaluate the antioxidant activity of extract obtained from allspice leaves and the effects of its addition in mechanically separated poultry meat (MSPM) and subsequent use in an emulsified meat product. The extract has a high antioxidant by the methods of DPPH (0.051 ± 0.004 mg/mL-1), ABTS (25.18 ± 1.79 mmol trolox/g de extract) and TBARS (28.60% antioxidant content). Three other blends were prepared from the pure extract, with different proportions of additives (M1, M2 and M3), and added to the MSPM. A portion of MSPM was stored (4 °C) for 9 days, and another portion was cooked and stored (4 °C) for 3 days. In the fresh MSPM, there was an interaction (P < 0.05) of treatment versus time in pH, peroxide index and TBARS index. At the end of storage, the highest TBARS values were observed for the control treatment (2.23 ± 0.11 mg MAD/kg). The lipid oxidation was by the treatments, with the M1 treatment presenting the lowest average value (0.87 ± 0.01 mg/kg). There was only a significant (P < 0.05) effect of storage time for all color indexes, wherein the values of L*, a*, b* and C * decreased over time and h * values showed a significant increase. For cooked MSPM, a significant interaction (P < 0.05) of treatment versus time was observed for IP and TBARS values. The IP average increased at the end of time only in M1 and M2 treatments, rising from 40.87 ± 0.67 mg CHP/kg to 47.59 ± 0.28 mg CHP/kg. The TBARS values at the end time was higher (P < 0.05) for the control (6.30 ± 0.06 mg MAD/kg) and lower (P < 0.05) for M1 and M3 treatments (1.43 ± 0.20 mg MAD/kg). Finally, the MSPM with the treatments were used in the mortadella’s preparation its evaluation at 0 and 30 days of storage (4 ° C). There was an interaction (P < 0.05) of treatment versus time only for TBARS values. At 30 days of storage, TBARS values were higher (P < 0.05) in the control treatment (1.69 ± 0.03 mg MAD/kg), followed by M2 (1.57 ± 0.05 mg MAD/kg) and by the other treatments (1.40 ± 0.04 mg MAD/kg). It was concluded that the use of the extract of allspice leaves has a high potential as an antioxidant in the MSPM storage and its subsequent use in emulsified product, extending its shelf life based on the lipid oxidation, wherein the mixture M1 proved to be the most suitable.